Study on Urban Growth of Pakse City: https://doi.org/10.69692/SUJMRD1004144 - SENGONKEO, Luangphasy; CHITPANYA, Soukanh; VENVONGTHONG, Phonguen; INTHAVONG, Daohieng; SIHAVONG, Saikhim (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research has considered the growth and important changes of Pakse city in Lao PDR from 2005 to 2020. The city is strategically located as a commercial and tourism center in the Mekong sub-region. In addition, Pakse's rapid urban growth is fueled by economic development, infrastructure improvements, demographic changes and strategic geographic location, all of which contribute to making it an important urban center in the south. The research aims to study the growth of the city of Pakse to create an understanding of the phenomenon, the driving force as well as the factors that lead to the growth of the city as a way to plan and control the development of the city for sustainable growth using the integrated research method of spatial analysis, quantitative analysis and document survey which analyzes the growth of the population and households, economic growth and the growth of the urban area. The analysis results show a population increase of 32.30 percent (from 78,669 people in 2005 to 116,200 people in 2020). Economic growth is also clear GDP per capita increased by 56.86 percent (from 1,097 dollars in 2005 to 2,543 dollars in 2020). The growth of the construction area of ​​the city increased by 47.03 percent (from 285 hectares in 2005 to 538 hectares in 2020) and in Pakse city municipality, there is a growth of 46.35 percent (from 279 hectares to 520 hectares in 2020). Most of the built-up area is concentrated in the city center, covering 96.65 percent, and the number of buildings has increased by 45.18 percent (from 17,262 to 30,870 in 2020). These findings indicate the growth of Pakse city during the study period.